Inter-connecting Aboriginal and Western Paradigms in Post-secondary Science Education: An Action Research Approach - Hogue, Michelle Marie (Journal of the Canadian Association for Curriculum Studies, 2012)
Very few Aboriginal[1] students are successful in science courses in the Western education system, particularly at the post-secondary level. Without a science background they are excluded from entering into science-related professions such as medicine, scientific research, science education, fields of engineering environmental and biological sciences to name a few. The result has been the severe under-representation of Aboriginal people and their voice in such professions. The vast array of literature that addresses the issue of Aboriginal success in post-secondary education is quantitative in nature and done “on” Aboriginal people by non-Aboriginal people. Very little qualitative data exists, that addresses this issue from the experiential voice and perspective of the Aboriginal people themselves. This paper addresses the results of focus group discussions with Aboriginal students, faculty, teachers and community members around the issue, from their perspective and voice, of what is needed for Aboriginal success in post-secondary education with a specific focus on science. [1] The research for this project was done in collaboration with members of the surrounding Blackfoot community, the Aboriginal community indigenous to Southern Alberta. The words Aboriginal, Indigenous, Native will be used interchangeably within this paper and are meant to be inclusionary of Aboriginal peoples. Blackfoot specifically refers to members of the surrounding Aboriginal community involved in this project.